Why Do Line Drawings Work? A Realism Hypothesis. (April 2020) - Hertzmann, Aaron
Why is it that we can recognize object identity and 3D shape from line drawings, even though they do not exist in the natural world? This article hypothesizes that the human visual system perceives line drawings as if they were approximately realistic images. Moreover, the techniques of line drawing are chosen to accurately convey shape to a human observer. Several implications and variants of this hypothesis are explored.